The South African Nursing Council: Aspects of its development 1944-1984 - Wilma J Kotzé (Curationis, 1985)
In a memorandum submitted to the Commission on National Health Services in 1943 the Organising Secretary of the South African Trained Nurses’ Association, Mrs. Sharley Cribb, wrote the following, quoted from the South African Nursing Journal, February 1943